Cytotoxic and targeted therapy for treatment of pseudomyogenic hemangioendothelioma. Issue 1 (December 2015) - Joseph, Jason; Wang, Wei-lien; Patnana, Madhavi; Ramesh, Naveen; Benjamin, Robert; Patel, Shreyaskumar; Ravi, Vinod
Abstract Pseudomyogenic hemangioendothelioma (PMH) is a recently described, indolent vascular tumor that usually presents in the distal extremities. PMH typically has a multi-focal presentation and can involve several tissue planes including the dermis, subcutis, muscle, and bone. This soft tissue tumor predominantly affects men between 20 and 50 years of age. PMH tumors typically are resected but frequently recur locally; thus, more efficacious treatment options are needed. Herein, we report two cases of patients with PMH who were treated with systemic therapy. To the best of our knowledge, our report is the first to describe a response of PMH either to gemcitabine/taxane cytotoxic chemotherapy or to a mammalian target of rapamycin inhibitor. In the first case, a 45-year-old man with PMH of the right ilium was treated with gemcitabine plus docetaxel. Although chemotherapy was ultimately halted owing to gemcitabine-induced pulmonary toxicity, positron emission tomography-computer tomography scans taken after three cycles of gemcitabine plus docetaxel illustrated a noticeable response to the regimen. In the second case, a 22-year-old man with PMH of the right distal femur and metastases in the left ilium showed no response to gemcitabine plus docetaxel therapy, but underwent surgical resection after cisplatin and doxorubicin resulted in stable disease. DNA sequencing of his tumor revealed the presence of a tuberous sclerosis 1 (TSC1) mutation, so daily everolimus, which inhibits mammalian target of rapamycin, was started. Two months after beginning everolimus, the patient underwent magnetic resonance imaging of the pelvis, which revealed mild shrinkage of PMH metastases in the left iliac bone. Despite the apparent heterogeneity of response to gemcitabine/taxane chemotherapy in our two patients, these two cases indicate that gemcitabine/taxane and mammalian target of rapamycin inhibitor may serve as systemic treatment options for PMH and warrant further investigation.